A Broad Doorway to the Big Tent: A Four-Strand Model for Discipline-Based Faculty Development on Inquiry-Based Learning. Issue 4 (21st April 2023) - Yoshinobu, Stan; Jones, Matthew G.; Hayward, Charles N.; Schumacher, Carol; Laursen, Sandra L.
ABSTRACT: Faculty professional development is an important lever for change in supporting instructors to adopt research-based instructional strategies that engage students intellectually, foster learning-supportive attitudes and habits of mind, and strengthen their persistence in mathematics. Yet the literature contains few well-rationalized models for faculty development in higher education. We describe the rationale and design for a model for discipline-based faculty development to support instructional change, and we detail our implementation of this model as applied to intensive workshops on inquiry-based learning (IBL) in college mathematics. These workshops seek to foster post-secondary mathematics instructors' adoption of IBL, to help them adapt inquiry approaches for their classrooms, and ultimately to increase student learning and persistence in science and mathematics. Based on observed faculty needs, four strands of activity help instructors develop a mental model for an IBL classroom, adapt that model to their teaching context, develop facilitation and task-design skills, and plan an IBL mathematics course. Evaluation data from surveys and observations illustrate participant responses to the workshop and its components. The model has been robust across 15 years of workshops implemented by three generations of workshop leaders and its features make it adaptive, strategic, and practical for other faculty developers.